Herbs as antimicrobial remedies and the scientific evidences. - Mohd Hassan, Norazian; Ahmed, Qamar Uddin (IIUM Press, 2011)
Herbs has long been traditionally proved as effective remedies in preventing and treating various microbial infectious diseases, such as ringworm, Athlete's foot, nail infections, scalp infections, vaginal and oral infections. The successful experience of using herbs as antimicrobial agents has been shared throughout generations and has guided the modem generations in using herbs as an alternative therapy to\:vards conventional antimicrobial agents. The traditional use of certain herbs in treating infections also has been proved and supported with scientific evidences through ethnopharmacologyand reverse pharmacology studies. Some herbs are also proved to be used as safe home remedies as practiced traditionally through evidences from scientific studies.